A quick guide for computer-assisted instruction in computational biology and bioinformatics - Costa, Manuel João (2008)
Introduction: Computational Biology and Bioinformatics (CBB) are indispensable components in the training of life scientists [1–3]. Current curricula in the life sciences should prepare graduates who master quantitative and computer skills for increased levels of performance [4–6]. Equally important is that the application of the curricula is driven by an appropriate instructional paradigm and effective learning experiences. Teaching and learning with computers bring specific issues that should be considered beforehand by any instructor. The following Quick Guide for Computer-Assisted Instruction (CAI) outlines ten principles for effective teaching. The principles are aligned with current developments on human cognition and learning [7] and have been drawn from our own experience using CAI in seminars, tutorials, and distance education, in courses on Molecular Life Sciences at the undergraduate level, taught to majors in biology or in other subjects (e.g., nutrition, teaching of physics and chemistry, teaching of biology, sports). The Guide refers to the preparation, presentation, and assessment of CAI. It should be an aid for those who teach CBB with CAI in class, and it is expected to stimulate student motivation and deeper learning in CBB, thus making class time more effective and improving satisfaction of both students and instructors.